Antiangiogenic activity of trabectedin in myxoid liposarcoma: Involvement of host TIMP‐1 and TIMP‐2 and tumor thrombospondin‐1. Issue 3 (19th June 2014) - Dossi, Romina; Frapolli, Roberta; Di Giandomenico, Silvana; Paracchini, Lara; Bozzi, Fabio; Brich, Silvia; Castiglioni, Vittoria; Borsotti, Patrizia; Belotti, Dorina; Uboldi, Sarah; Sanfilippo, Roberta; Erba, Eugenio; et al.
<x xml:space="preserve">Abstract</x> Trabectedin is a marine natural product, approved in Europe for the treatment of soft tissue sarcoma and relapsed ovarian cancer. Clinical and experimental evidence indicates that trabectedin is particularly effective against myxoid liposarcomas where response is associated to regression of capillary networks. Here, we investigated the mechanism of the antiangiogenic activity of trabectedin in myxoid liposarcomas. Trabectedin directly targeted endothelial cells, impairing functions relying on extracellular matrix remodeling (invasion and branching morphogenesis) through the upregulation of the inhibitors of matrix metalloproteinases TIMP‐1 and TIMP‐2. Increased TIMPs synthesis by the tumor microenvironment following trabectedin treatment was confirmed in xenograft models of myxoid liposarcoma. In addition, trabectedin upregulated tumor cell expression of the endogenous inhibitor thrombospondin‐1 (TSP‐1, a key regulator of angiogenesis‐dependent dormancy in sarcoma), in in vivo models of myxoid liposarcomas, in vitro cell lines and primary cell cultures from patients' myxoid liposarcomas. Chromatin Immunoprecipitation analysis showed that trabectedin displaced the master regulator of adipogenesis C/EBPβ from the TSP‐1 promoter, indicating an association between the up‐regulation of TSP‐1 and induction of adipocytic differentiation program by trabectedin. We conclude that trabectedin inhibits angiogenesis through multiple mechanisms, including directly affecting endothelial cells in the tumor microenvironment—with a potentially widespread activity—and targeting tumor cells' angiogenic activity, linked to a tumor‐specific molecular alteration.